Tracheal and lower airway changes in a patient with mucolipidosis type II. Issue 7 (8th April 2020) - Poore, Thomas S.; Prager, Jeremy; Weinman, Jason P.; Larson, Austin; Houin, Paul
Abstract: Introduction: Mucolipidosis type II (MLII) is a lysosomal storage disease causing systemic deposition of mucopolysaccharides. We describe imaging and bronchoscopy findings not previously reported in the literature in a child with MLII. Case: A 9‐year‐old with MLII s/p hematopoietic stem‐cell transplant (HSCT), bronchiectasis, and aspiration presented with recurrent respiratory illnesses. Bronchoscopy and chest computed tomography were performed, showing a saber‐sheath trachea with fixed narrowing and curvature. Discussion: This case describes potentially life‐threatening airway distortion in MLII despite HSCT that cannot be ameliorated with tracheostomy. Etiology is unknown but likely due to abnormal deposition causing an immobile, stenotic airway and restricted thorax.